Strategy In The Islamic Capital Market (2024) - Gumala Defa , Kikim (Jurnal Ekonomi Islam, Akuntansi, dan Manajemen, 2024)
The purpose of this research is to analyze the problem which then becomes a strategic step in the form of an action plan for the development of the Islamic capital market which has increased from year to year. The research method used is a literature study based on journals. Data collection is done through Focus Group Discussion (FGD). Furthermore, the data that has been collected is analyzed using Urgency, Seriousness, and Growth (USG) analysis. Based on the USG analysis, there are problems that occur that can hinder the development of Islamic capital markets in Indonesia. The problems focused on include an economic system that has not supported, lack of knowledge of investment products in the Islamic capital market, inadequate public perception due to lack of literacy, trust issues on Islamic products and lack of regulation. From these problems, a work action plan was made as a solution which eventually became the development strategy of the Islamic capital market in Indonesia. The fishbone diagram is used to find out the strategy in optimizing the development of the Islamic capital market which starts from the problem of the development of the Islamic capital market in Indonesia. The fishbone diagram shows the problems that become a reference in the development strategy of the Islamic capital market in Indonesia.